UPAYA TUTOR DALAM MENINGKATKAN MOTIVASI BELAJAR WARGA BELAJAR PAKET C DI PKBM BUNGA TANJUNG DESA TANJUNG RAMBUTAN KECAMATAN KAMPAR KABUPATEN KAMPAR - Devi Yusmasari; Aswandi Bahar; widiastuti ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstrak: This study aims to determine tutor efforts in improving the learning motivation of citizens to learn the package C in PKBM Bunga Tanjung Desa Tanjung Rambutan Kecamatan Kampar Kabupaten Kampar. This research is a qualitative descriptive naturalistic approach.. This research was conducted in PKBM Bunga Tanjung Desa Tanjung Rambutan Kecamatan Kampar Kabupaten Kampar. The source of the data in this study amounted to 4 people consisting of tutors, managers and citizens learn. Data collection techniques using observation, interviews, and documentation. The results showed that tutors efforts in improving the learning motivation of citizens to learn the package C in PKBM Bunga Tanjung Desa Tanjung Rambutan Kecamatan Kampar Kabupaten Kampar quite well, from the indikator (1) The effort of moving the motivation, The efforts made in the move tutor learning motivation of citizens learning package C belongs to the already good enough. Due to the efforts made by the maximum already tutor moves the interest and attention of citizens learning and creating an effective classroom so that citizens learn to feel comfortable following the learning process (2) Efforts Of Hope, Efforts are being made tutor in hopes of giving classified either because tutors formulate learning objectives as specific as possible so that the learners can achieve the expected results. Tutors also provide information which can improve learning motivation of citizens to learn Package C. (3) Efforts incentives, Efforts are being made tutor in the provision of incentives are good enough, because the tutors make efforts so that the learners have progress in learning, as for the efforts made in the provision of incentives which provide feedback on tests, reward and encouragement orally or in writing, commenting on the the results of the work and cooperation among the learners.Keywords: Tutor Efforts in Improving Motivation